Malestares y adaptaciones positivas de docentes de la Universidad de Costa Rica en tiempos de Pandemia por COVID-19 - Cordero Cordero, Teresita (Universidad de Costa Rica, 2022)
This research seeks to identify the strains on professors generated by confinement and adjustments in family life as a result of the new labor demands in the framework of the 2020-2021 pandemic. Fears of illness and death from COVID-19, as well as confinement, have generated a series of effects on health and daily life within the national and international population. The qualitative research was generated through open, in-depth interviews with 11 teachers from five academic units or schools of the Faculties of Social Sciences and Education of the University of Costa Rica (UCR). One of the inclusion criteria was defined as the teaching staff who best assumed the virtual work, and those who expressed discomfort or difficulties. The transcribed material was coded using the qualitative analysis package Nvivo, as follows: expression of feelings generated by the circumstances experienced; home office arrangements and adjustments; and expressions of self-care and self-discipline. The stories describe organizational systems at home, the positive and negative effects of living with health restrictions, and concerns related to the student body, as well as manifestations of fatigue, anguish, sedentary lifestyles, and fears, among others. Positive changes favored academic work, exercise and diet. The organization of the academic units and support among colleagues were described positively, and the findings confirm the importance of caring not only for physical health, but also mental health.